2021
DOI: 10.1080/1554480x.2021.1897012
|View full text |Cite
|
Sign up to set email alerts
|

The ateneo as an effective model of continuing professional development: findings from southern Argentina

Abstract: Despite a sustainable research interest in different forms of teachers' professional development, scant international attention has been paid to forms of professional development which are implemented in South America. Based on a qualitative research design, this study explores the impact of the ateneo as an innovative model of continuing professional development. An ateneo is a model which supports teacher reflection and change in teaching practices by concentrating on context-responsive practical issues such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mentoring was also seen as a dynamic activity (Extract 10). In line with the literature on mentoring as a form of CPD with early career teachers (Banegas, 2022;Banegas & Glatigny, 2021;Gakonga, 2019;Johnson, 2006;Messiou & Ainscow, 2020), the analysis of the data from teachers of varying degrees of experience revealed that mentoring was viewed as a "valid way of CPD" (Antonella, Journal, Extract 11). Furthermore, some mentees seemed to change their minds, such as Gabriela, who had negative feelings towards traditional CPD (Extract 12), but after the study, she saw mentoring as an excellent alternative to CPD (Extract 13).…”
Section: Extractmentioning
confidence: 59%
See 1 more Smart Citation
“…Mentoring was also seen as a dynamic activity (Extract 10). In line with the literature on mentoring as a form of CPD with early career teachers (Banegas, 2022;Banegas & Glatigny, 2021;Gakonga, 2019;Johnson, 2006;Messiou & Ainscow, 2020), the analysis of the data from teachers of varying degrees of experience revealed that mentoring was viewed as a "valid way of CPD" (Antonella, Journal, Extract 11). Furthermore, some mentees seemed to change their minds, such as Gabriela, who had negative feelings towards traditional CPD (Extract 12), but after the study, she saw mentoring as an excellent alternative to CPD (Extract 13).…”
Section: Extractmentioning
confidence: 59%
“…From a sociocultural perspective, and in the ELT context, in particular, mentoring has been regarded as a form of CPD-teachers build knowledge through mentor-mentees' interaction provided teachers have the affordance to do so (Banegas, 2022;Banegas & Glatigny, 2021;Gakonga, 2019;Johnson, 2006;Johnson & Golombek, 2011;Messiou & Ainscow, 2020;Williams et al, 2015). Mentoring offers guided reflection and emotional and technical support (Gakonga, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Given the multifaceted nature of the lesson planning mechanism, student agent and technology creates new opportunities or provides affordance in the teacher environment, where teachers are supposed to shoulder the responsibility to align objectives, instruction, and assessment. In addition, lesson planning would present a bigger picture, encompassing the collective and personal (de)construction of teachers' practices and the development of contextualized and pedagogically informed interventions [18]. Particularly, the cooperation between teachers and the policy-supported programs allow teachers to experience a supportive learning environment which impacted on their agency as autonomous, yet community-driven, professionals of English language teaching, achieving an improvement in lesson contextualization, sequencing and transitioning, maximization of resources, class time management, and reflective teaching [18].…”
Section: Understanding Complexity Theorymentioning
confidence: 99%